Plasmonic Metalens‐Enhanced Single‐Mode Fibers: A Pathway Toward Remote Light Focusing - Matthias Zeisberger (Wiley-VCH, 2021)
The focusing of light represents a key functionality, which can efficiently be achieved through wavefront shaping via metasurfaces (MSs). Remote light focusing requires interfacing these ultraflat photonic structures with optical fibers, which is hard to achieve due to fabrication limitations and challenging beam management. Herein, the successful interfacing of a focusing plasmonic metalens with a regular single‐mode step‐index fiber through modified electron beam lithography is demonstrated. Specifically, a plasmonic MS consisting of nanoslots is realized on the end face of a modified single‐mode fiber via planarization and e‐beam lithography. A key feature of the device is the introduction of a coreless glass section in between the fiber and MS, which allows for free beam expansion up to 48 μm to fully exploit the numerical aperture (NA) of the metalens. In agreement with simulations, a clear focus with a NA of about 0.3 is found in the experiments, confirming the successful realization of a plasmonic metalens‐enhanced single‐mode fiber. Due to its unique properties, this concept finds applications in a multitude of areas, examples of which include optical trapping, generation of sophisticated beam profiles, and boosting light coupling efficiencies.